POLITENESS NORMS FOR HARMONIOUS COMMUNICATION WHEN SERVING TOURISTS IN CENTRAL JAVA - Purnomo, Budi (KOMUNITAS, 2014)
People in most cultures would probably agree that politeness is needed during their interaction. However there may be differing opinions as to when they should be polite. In tourism industry, tourism serviceproviders act as host and tourists act as guests. Typically hosts will try to act politely and use appropriate politeness norms whenÂ  communicatingÂ  withÂ  guestsÂ  toÂ  ensureÂ  harmonious communication.Â  TheÂ  researchÂ  findingsÂ  showÂ  thatÂ  thetourism service providers in Central Java use variousÂ  unggah-ungguhâpoliteness normsâ when serving English speaking tourists and Indonesian speaking tourists.Besides that, there are some violations made by the tourism serviceÂ  providersÂ  inÂ  usingÂ  unggah-ungguhÂ  âpolitenessÂ  normsâ.Â  TheÂ  researchÂ  findingsÂ  alsoÂ  show thatÂ  thereÂ  are similar and different perspectives onÂ  unggah-ungguhâpoliteness normsâ between English speaking tourists with Western culture background and Indonesian speaking tourists with Indonesian culture backgrounds towards the politenessÂ  normsÂ  usedÂ  byÂ  theÂ  tourismÂ  serviceÂ  providersÂ  inÂ  CentralÂ  Java.Â  TheÂ  findingsÂ  implyÂ  theÂ  needsÂ  of improvingÂ  unggah-ungguhÂ  âpolitenessÂ  normsâÂ  implementationÂ  whichÂ  isÂ  discoveredÂ  fromÂ  wellÂ  knownÂ  noble Javanese culture used by the tourism service providers when serving tourists. Keywords:politeness norms, harmonious communication, English and Indonesian tourists